Importance of Life Insurance For Policy Holders: Understanding Purchasing Patterns and Preference among Policy Holders (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The pattern of consideration of different reasons of purchasing an insurance policy was found to be similar in the three regions under study as was observed in case of total policy holders. However, less premium was considered by a significantly higher proportion of 3RD policy holders (62.00%) as compared to 1ST policy holders (48.00%). Though less premium attracted  the  attention  of  policy  holders  in  all  the  regions  but  it  was  at  the highest level im 3RD region.